Consensus Bundle on Postpartum Care Basics: From Birth to the Comprehensive Postpartum Visit. Issue 4 (December 2021) - Stuebe, A.M.; Kendig, S.; Suplee, P.D.; D'Oria, R.
Abstract : ( Obstet Gynecol. 2021;137:33–40) Postpartum care is an underutilized resource, with up to 23% of women forgoing a clinic visit in the weeks following delivery. Given the increased maternal morbidity and mortality postpartum, the Alliance of Innovation in Maternal Health developed a set of strategies to improve outcomes for postpartum women. This "consensus bundle" includes recommendations for Readiness, Recognition, Response and Reporting.